Best practices : Australian clinical legal education : the final report of the project, Strengthening Australian Legal Education by Integrating Clinical Experiences : Identifying and Supporting Effective Practices. - Evans, Adrian; Cody, Anna; Copeland, Anna; Giddings, Jeff; Noone, Mary Anne; Rice, Simon; Booth, Ebony (Office for Learning and Teaching, 2013)
Final report from a project that sought to develop standards for effective clinical legal education in their own right and to assist in renewal of University law curricula in Australia. The project investigated current practices in clinical programs in six Australian jurisdictions with participation from six law schools closely identified with experiential learning in law. Workshops across Australia explored the disparate and uneven approaches to clinical learning and effective practice. The findings from each jurisdiction were also workshopped, compared and contrasted among key stakeholders, resulting in these deliverables: the production of recommended standards for current and new clinical programs, a national conference and an edited book. In this way, law deans' and academics' consciousness of the importance of experiential learning to renewal of law curricula was disseminated across Australia.